Risk factors for perinatal mortality: a case control study from Thiruvananthapuram, Kerala, India - Brahmanandan, Mayadevi; Murukesan, Lekshmi; Nambisan, Bindu; Salmabeevi, Shaila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The greatest risks to life are in its very beginning. Although a good start in life begins well before birth, it is just before, during, and in the very first hours and days after birth that life is most at risk. This prospective case control study was designed on maternal risk factors for perinatal mortality. Methods: This was a case control study conducted in the Department of Obstetrics and Gynecology and Department of Paediatrics, Medical College Trivandrum for one year period in 2004-2005. The cases were all the fresh and macerated still births and early neonatal death cases during the study period. The controls were chosen as the next delivery entry in the OR register. Results: During this period, the total number of deliveries was 14,796 and there were 431 perinatal deaths. The perinatal mortality rate was 29.12. This was much higher compared to Kerala’s perinatal mortality rate of 10, the reason being that the study is conducted in a tertiary referral hospital with one of the best new born care nurseries and a large number of referrals. The most significant risk factors for perinatal mortality were low socio-economic status, referrals, late registration, prematurity, low birth weight, intra-uterine growth restriction, maternal diseases like gestational hypertension and gestational diabetes and intrapartum complications like abruption. Conclusions: Perinatal mortality rate serves as the most sensitive index of maternal and neonatal care. Good antenatal care and prevention of preterm birth may play a key role in further reduction of PMR.